Improving vehicular ad hoc networks (VANET) communication performance by using time gap following distance (TGFD) model - Fadilah, Suzi Iryanti; Abd Wahab, Mohd Helmy; Mohd Shariff, Azizul Rahman; Mohd Zaini, Khuzairi; Shibghatullah, Abdul Samad (2016)
Today, there is a growing research study of IEEE 802.11p as one of option to help the drivers to travel more safely.Message dissemination protocols are primordial for safety vehicular applications. Periodic safety message (PSM) and Warning safety message (WSM) are two types of safety messages which may be exchanged between vehicles. In this paper we investigate the feasibility of deploying safety applications based on periodic message dissemination through simulation study with safety requirements as our priority concern.Vehicles are supposed to issue these messages constantly to inform their neighboring vehicles about their current status and use received messages for preventing possible unsafe situations on time. As reliability is the main concern in periodic message dissemination, a new metric called TGFD (Time Gap Following Distance) is defined which gives us more accurate benchmark for evaluating QoS in safety applications specifically.Thus, in order to improve the performance, the effective transmission TGFD studied.